Pelatihan CapCut sebagai Upaya Pengembangan Video Pembelajaran Digital Pada MGMP Matematika Tingkat SMP Lhokseumawe - Mahmuzah, Rifaatul; Zahara, Yulia; Ardian, Zalfie; Ningtiyas, Fitri Ayu; Sinaga, Nurul Afni (MALLOMO: Journal of Community Service, 2025)
Abstract. The development of digital technology has opened up opportunities for innovation in learning, including in teaching mathematics at the junior high school level. However, many teachers still face limitations using interactive digital media. This training activity aims for helping Junior High School Mathematics teachers MGMP in Lhokseumawe City to improve their skills to edit and develop digital learning videos using the CapCut application. The implementation method consists of a needs survey, technical training in two meetings, mentoring, and evaluation of training results. The results of the activity showed a significant increase in teachers' understanding and skills in utilizing CapCut, so that they can produce more interesting, and interactive learning media. Evaluation of the training indicated high satisfaction from participants, with most teachers feeling helped in improving their creativity and learning effectiveness. Recommendations from participants include the need for further training with a scope of other digital applications. In conclusion, this CapCut training has proven to be effective in improving teacher competence in the use of digital technology for learning. This training is expected to improve teacher competence in the field of educational technology and support more effective and innovative digital-based learning. Abstrak. Perkembangan teknologi digital telah membuka peluang bagi inovasi dalam pembelajaran, termasuk dalam pengajaran matematika di tingkat Sekolah Menengah Pertama. Namun, banyak guru masih menghadapi keterbatasan dalam pemanfaatan media digital interaktif. Kegiatan pelatihan ini bertujuan untuk membekali guru MGMP Matematika Tingkat SMP Kota Lhokseumawe dengan keterampilan mengedit dan mengembangkan video pembelajaran digital menggunakan aplikasi CapCut. Metode pelaksanaan terdiri dari survei kebutuhan, pelatihan teknis dalam dua pertemuan, pendampingan, dan evaluasi hasil pelatihan. Hasil kegiatan menunjukkan peningkatan signifikan dalam pemahaman dan keterampilan guru dalam memanfaatkan CapCut, sehingga mereka dapat menciptakan media pembelajaran yang lebih menarik, dan interaktif. Evaluasi terhadap pelatihan mengindikasikan kepuasan tinggi dari peserta, dengan sebagian besar guru merasa terbantu dalam meningkatkan kreativitas dan efektivitas pembelajaran mereka. Rekomendasi dari peserta mencakup perlunya pelatihan lanjutan dengan cakupan aplikasi digital lainnya. Kesimpulannya, pelatihan CapCut ini terbukti efektif dalam meningkatkan kompetensi guru dalam pemanfaatan teknologi digital untuk pembelajaran. Pelatihan ini diharapkan dapat meningkatkan kompetensi guru di bidang teknologi pendidikan serta mendukung pembelajaran berbasis digital yang lebih efektif dan inovatif.